The Influence of The Speaker's and Hearer's Age on Request Strategies Used in the Movie Yours, Mine & Ours - Salsabila, Aflah Nuraini; Basuki, Amin (Lexicon, 2024)
This research aims to analyze request strategies in the movie Yours, Mine & Ours (2005). In particular, it attempts to identify and classify request strategies used by the main characters in the movie using the theory of request strategies proposed by Blum-Kulka and Olshtain (1984). This research also analyzes the differences of request strategies influenced by speaker's and hearer's age which are divided into four age groups: adult, teenager, pre-teen, and children. The data used in this research are all utterances containing requests made by the main characters in the movie. In Yours, Mine & Ours, the requests occur in the family domain and informal situations. The results show that the strategy that is most used by all age groups is Mood Derivable, which belongs to Direct Strategy. It also shows that adult is the age group that uses Direct Strategy the most and uses more types of strategy than the other age groups. Furthermore, the research also found that all age groups prefer to use Mood Derivable when the hearer is from the same and younger age group. Meanwhile, when the hearer is from older age group, the speaker prefers to use Reference to Preparatory Conditions.